APPROACHES TO UNDERSTANDING THE PHENOMENON OF TOLERANCE IN CROSS-CULTURAL RESEARCHES - Yangiboyeva Dildoraxon Rahmon qizi; Gapparova Mastona Safaraliyevna (Journal Park Publishing, 2022)
In different languages, depending on the historical experience of peoples, the general content of the concept of tolerance has different shades of meaning: - in English tolerance is "readiness and ability to accept a person or thing without protest"; - in French - "respect for freedom of the other, his way of thinking, behavior, political and religious views"; - in Chinese tolerance means "to allow, allow, show generosity towards others"; - in Arabic tolerance is "forgiveness, condescension, mildness, indulgence, compassionate tolerance"; - in Persian it means "patience, tolerance, endurance"; - in Arabic it means "forgiveness, indulgence, leniency, forbearance".